2020
DOI: 10.1029/2019jd031684
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Global Sources of Atmospheric Ammonia from Agricultural Soils

Abstract: Global ammonia (NH 3 ) emissions to the atmosphere are projected to increase in the coming years with the increased use of synthetic nitrogen fertilizers and cultivation of nitrogen-fixing crops. A statistical model (NH 3 _STAT) is developed for characterizing atmospheric NH 3 emissions from agricultural soils and compared to the performance of other global and regional NH 3 models (e.g., Emission Database for Global Atmospheric Research, Magnitude and Seasonality of Agricultural Emissions, MIX, and U.S. Envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…During the period 2002–2016, significant increases in NH 3 emissions were observed over several of the world’s major agricultural regions [ 3 ]. Approximately 80% of global NH 3 emissions are a result of anthropogenic sources (animal and crop agriculture) [ 4 ]. In Ireland, agriculture is responsible for 99.1% of NH 3 emissions, with the application of animal manures accounting for 90% of the total figure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the period 2002–2016, significant increases in NH 3 emissions were observed over several of the world’s major agricultural regions [ 3 ]. Approximately 80% of global NH 3 emissions are a result of anthropogenic sources (animal and crop agriculture) [ 4 ]. In Ireland, agriculture is responsible for 99.1% of NH 3 emissions, with the application of animal manures accounting for 90% of the total figure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia (NH 3 ) and its salts are major contributors to eutrophication, and corresponding abatement strategies might lead to increased greenhouse gas (GHG) emissions [2]. Agriculture, mainly livestock production, is the greatest contributor to the emission of ammonia (NH 3 ) [2][3][4]. The GHGs from animal husbandry are nitrous oxide and methane.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is mainly produced by enteric fermentation and manure storage, and has an effect on global warming 28 times higher than carbon dioxide [5]. The general demand for measures to abate emissions of NH 3 due to the 2 of 14 rise in livestock production has led to the development of various manure management strategies, at different stages of the manure management chain (animal diets and housing, manure treatment, storage, and application) [3,6]. Livestock production is projected to double in the next century to accommodate the growing world population [7], which is expected to reach 9 billion by 2050 [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long history of repetitive grass burning of vegetal material may have facilitated selection of thermophilic carboxydotrophic bacteria that comprise the unique metabolisms observed in our CNF consortium. Several sources, including biomass burning, are responsible for the emission of CO, CO 2 , H 2 , NOx, N 2 O, and NH 3 27 , which may have enhanced the microorganisms that are able to grow without any source of organic carbon and nitrogen by consuming gaseous atmosphere (CO, N 2 , and O 2 ). The persistence of the less-abundant taxa observed over the continuum replication process (>3 years) indicated that the organisms are either complementing each other’s metabolism or are benefiting from the secondary metabolites from different players.…”
Section: Discussionmentioning
confidence: 99%